Low Rates of Survival Seen in Orthopedic Patients Receiving In-Hospital Cardiopulmonary Resuscitation. (14th January 2019) - Fletcher, James W. A.; Smith, Adam; Walsh, Katherine; Riddick, Andrew
Introduction: Despite awareness of overall poor survival rates following cardiopulmonary resuscitation (CPR), some orthopedic patients with significant comorbidities continue to have inappropriate resuscitation plans. Furthermore, in certain injury groups such as patients with hip fractures, survival outcome data are very limited; current discussions regarding resuscitation plans may be inaccurate. This study assesses survival in orthopedic patients following CPR, to inform decision-making between physicians, surgeons, and patients. Methods: A dual center, retrospective cohort study was performed analyzing all orthopedic admissions that received CPR over a 25-month period, with a minimum of 1 year follow-up. National Cardiac Arrest Audit data, "mortality and morbidity" meeting records, National Hip Fracture Databases, and electronic notes were analyzed. Survival duration was measured, alongside reason for admission, location CPR occurred, and initial rhythm encountered. Results: Thirty-two patients received CPR over the 25-month period (median age: 83; range: 30-96). Three (9%) of 32 patients survived to discharge. Only 1 of the 26 patients older than 65 years survived to discharge. Fifteen (47%) of 32 had hip fractures, where 4 (27%) of 15 of this group survived 24 hours; none survived to discharge. When recorded, 22 (92%) of 24 initially had a nonshockable rhythm. Discussion: Cardiopulmonary resuscitation was conceptualized as a treatment for reversible cardiopulmonary causes. When used in trauma and orthopedic patients, especially older and/or hip fracture patients, it seldom led to hospital discharge. Different admission practices such as "front door" orthogeriatric reviews may explain the contrast in usage of CPR between the hospitals. Conclusion: Survival rates following CPR were very low, with it proving specifically ineffective in hip fracture patients. Although every decision about resuscitation should be patient centered and individualized, this study will allow clinicians to be more realistic about outcomes from CPR, particularly in the hip fracture group.